PENGARUH MONEY ETHICS DAN KEADILAN TERHADAP TAX EVASION DENGAN RELIGIOSITY SEBAGAI PEMODERASI - Theresia Liefa, Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2020)
This study was conducted to know the influence of money ethics and tax fairness against tax evasion and also to know the effects of intrinsic and extrinsic religiosity in their influence on money ethics and tax evasion. The primary data collection technique used was questionnaires to individual taxpayers at KPP Tambora. This research obtained 200 respondents as samples. In this research, there were 90 respondents that had been analyzed as samples. The sampling techniques used wasconvenience sampling. The analysis research using Smart-Partial Least Squares (PLS) 3.0. The result of the study showed that money ethics had not affect on tax evasion, however tax fairness had positive affect on tax evasion. Intrinsic religiosity and extrinsic religiosity as moderating variables did not succeed in moderating this relationship.